2013
DOI: 10.1021/jm401184f
|View full text |Cite
|
Sign up to set email alerts
|

Derivatives of Dibenzothiophene for Positron Emission Tomography Imaging of α7-Nicotinic Acetylcholine Receptors

Abstract: A new series of derivatives of 3-(1,4-diazabicyclo[3.2.2]nonan-4-yl)dibenzo[b,d]thiophene 5,5-dioxide with high binding affinities and selectivity for α7-nicotinic acetylcholine receptors (α7-nAChRs) (Ki = 0.4 – 20 nM) has been synthesized for PET imaging of α7-nAChRs. Two radiolabeled members of the series [18F]7a (Ki = 0.4 nM) and [18F]7c (Ki = 1.3 nM) were synthesized. [18F]7a and [18F]7c readily entered the mouse brain and specifically labeled α7-nAChRs. The α7-nAChR selective ligand 1 (SSR180711) blocked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
96
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(102 citation statements)
references
References 59 publications
4
96
1
Order By: Relevance
“…The binding assay of all four compounds was performed under the same assay conditions (Table 2). This head-to-head comparison demonstrated that the α7-nAChR affinity of ASEM is 1-2 orders of magnitude superior to the previous radiotracers[48] and in vivo specific binding of [ 18 F]ASEM was expected to be proportionally greater.…”
Section: Development Of [18f]asem[48 59]mentioning
confidence: 86%
See 4 more Smart Citations
“…The binding assay of all four compounds was performed under the same assay conditions (Table 2). This head-to-head comparison demonstrated that the α7-nAChR affinity of ASEM is 1-2 orders of magnitude superior to the previous radiotracers[48] and in vivo specific binding of [ 18 F]ASEM was expected to be proportionally greater.…”
Section: Development Of [18f]asem[48 59]mentioning
confidence: 86%
“…As summarized in the recent reviews[35, 46-48], those efforts did not lead to an α7-nAChR PET radioligand with sufficient in vivo specificity.…”
Section: Initial Pet Radioligands For α7-nachrsmentioning
confidence: 99%
See 3 more Smart Citations